Voegelin’s Escape from Legal Positivism: Constitutionalism and the Politico-Religious Problem - Kuź, Michał (Chrześcijaństwo-Świat-Polityka, 2024)
The following article deals with the polemic between Eric Voegelin’s political philosophy and the legal positivism of Hans Kelsen. The research question deals with the importance of this polemic, following a key text analysis. Based on Voegelin’s early writings, the Munich lectures and autobiographical reflection on his postgraduate studies, I argue that it is the critique of Kelsen’s legal positivism that gave Voegelin the initial impulse to develop his own philosophy of politics. Specifically, it led him to his project of investigating the basis of the functioning of different political bodies and to the conclusion that they are not structures which can be adequately researched without considering the absolute values (as elements of the “structure of being”). This philosophical reflection has a significant impact on the theory of law and constitutionalism; it however, does not provide a satisfactory answer to the practical politico-religious problem, or, in other words, the problem of theologizing and thus absolutizing ordinary politics.